Student self-determination and boundaries: An emerging market perspective on the development of sales skills - Wait, M.; Stiehler, B. (South African Journal of Higher Education, 2021)
In an emerging market economy faced with high unemployment rates, it is essential to develop entrepreneurial skills, of which sales skills have been identified as an imperative contributor. Applying self-determination theory and boundary theory, this study explores what motivates students enrolled in a direct selling practical module at a university to pass the module successfully in the form of reaching a sales target. It also explores the boundaries that students assign between their student and personal lives, and their perception of the skills they have developed on completion of the module. The research approach was qualitative and employed eight in-depth interviews. Inductive content analysis was used to analyse the data. The findings revealed enacted segmentation as students distinguish between their life/home and work/school roles, but are constantly aware of the module. It was also found that the students believe the module made a positive contribution to the development of several skills. The findings contribute on two levels: practically, it may aid educators who offer similar courses, or who operate in countries with similar challenges, with insights on how to improve their sales courses; and theoretically, it contributes to the development of theories applicable to emerging economies.